2015
DOI: 10.3389/fphys.2015.00233
|View full text |Cite
|
Sign up to set email alerts
|

Brain Gαi2-subunit proteins and the prevention of salt sensitive hypertension

Abstract: To counter the development of salt-sensitive hypertension, multiple brain G-protein-coupled receptor (GPCR) systems are activated to facilitate sympathoinhibition, sodium homeostasis, and normotension. Currently there is a paucity of knowledge regarding the role of down-stream GPCR-activated Gα-subunit proteins in these critically important physiological regulatory responses required for long-term blood pressure regulation. We have determined that brain Gαi2-proteins mediate natriuretic and sympathoinhibitory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 94 publications
(156 reference statements)
0
3
0
Order By: Relevance
“…To accomplish this goal, we first confirmed that 5-HT2C receptor expression was present in rat hippocampal neurons within the DG region. It has been reported that inhibitory G protein-coupled receptors play a key role in regulating the central and peripheral nervous systems [ 49 , 50 ]. Gαi-2 was shown to block the transient inhibition of mGluR2 on synaptic transmission and enhances LTD [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…To accomplish this goal, we first confirmed that 5-HT2C receptor expression was present in rat hippocampal neurons within the DG region. It has been reported that inhibitory G protein-coupled receptors play a key role in regulating the central and peripheral nervous systems [ 49 , 50 ]. Gαi-2 was shown to block the transient inhibition of mGluR2 on synaptic transmission and enhances LTD [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…The PI3K-Akt Pathway activation has been implicated to contribute to the progression of atherosclerotic plaque formation and pathological changes in the vasculature leading to hypertension and cardiovascular disorders in many studies ( 171 175 ). Several other cellular pathways associated with salt sensitive hypertension such as the WNK signaling pathway ( 176 ), Kelch-like 3/Cullin 3 ubiquitin ligase complex ( 177 ), brain Gαi2-proteins of GPCR ( 178 , 179 ) in the central nervous system, MAPK/extracellular signal regulated kinase [ERK] mediated by angiotensin II in vascular smooth muscles ( 180 ), and redox signaling ( 181 ) have been well elucidated.…”
Section: Dietary Salt In Hypertensive Heart Disease and Its Complicat...mentioning
confidence: 99%
“…G protein-coupled receptors activate heterotrimeric G proteins via ligand binding, thereby modulating the activity of cellular effectors and consequently regulating a wide array of cell functions 1 2 . The putative function of the functional class of G protein Gαi is defined by their ability to downregulate cAMP levels by inhibition of adenylyl cyclase 2 3 .…”
mentioning
confidence: 99%